Signal Analysis of Remote Control (RC) UAV Used Software Defined Radio (SDR) HackRF One - Yetti Yuniati; Ardian Ulvan; Sitronella Nurfitriani Hasim (Program Studi Sistem Informasi, 2019)
UAV (Unmanned Aerial Vehicle) is the unmanned aircraft which is controlled by Remote Control (RC) when flying. The operation of the UAV needs to be regulated to maintain air traffic security, one of which is by taking over the UAV. This study discussed the FSK modulation and demodulation mechanism in the process of taking over the UAV with HackRF One. The transfer mechanism of the UAV that done is to look for the RC frequency, channels, record the RC signals, determine the period and frequency carriers, and modelling the modulation and demodulation of FSK with Simulink. One parameter that is set in the process of this mechanism is to change the value of the different carrier frequencies. Then, the data obtained from the signal sent modulated results are the same as when the demodulated signal. Of T0= 79 μsandT1= 70 μs, so that fc0= 12658,22 Hz and fc1= 14285,71 Hz. To determine the size of the signal quality, it is necessary to determine the Bit Error Rate (BER) value. In this research, the obtained the BER values depend on the change of the energy value of Bit per Noise (Eb / No). When the Eb/No value is 10 (dB), then the BER is 0.038. Moreover, when the Eb/No value are 8 and 6 (dB), then the BER will be 0.078 and 0.23 respectively. It can be concluded that the greater Eb/No, the lower of BER.Keywords: UAV, Remote Control (RC), FSK Modulation, Simulink, HackRF One